2018
DOI: 10.1111/epi.14443
|View full text |Cite|
|
Sign up to set email alerts
|

Laser ablation for mesial temporal lobe epilepsy: Surgical and cognitive outcomes with and without mesial temporal sclerosis

Abstract: Seizure-free outcomes following LITT may be comparable in carefully selected patients with and without MTS, and these outcomes are comparable with outcomes following microsurgical resection. Failures may result from non-mesial components of the epileptogenic network that are not affected by LITT. Cognitive declines following MTL-LITT are modest, and principally affect memory processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 51 publications
(106 reference statements)
8
85
0
Order By: Relevance
“…[3][4][5][6][8][9][10][11][12] Unfortunately, without consideration of specific therapy location, which is subject to variability in patient anatomy and the surgery itself, these studies are limited in their ability to reliably report clinical outcomes. [3][4][5][6][8][9][10][11][12] Unfortunately, without consideration of specific therapy location, which is subject to variability in patient anatomy and the surgery itself, these studies are limited in their ability to reliably report clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][8][9][10][11][12] Unfortunately, without consideration of specific therapy location, which is subject to variability in patient anatomy and the surgery itself, these studies are limited in their ability to reliably report clinical outcomes. [3][4][5][6][8][9][10][11][12] Unfortunately, without consideration of specific therapy location, which is subject to variability in patient anatomy and the surgery itself, these studies are limited in their ability to reliably report clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Kang et al found no statistically significant difference in total ablated volume between seizure‐free and non–seizure‐free patients among their 14 MTS patients, nor of specific structures including hippocampus, amygdala, entorhinal cortex, parahippocampal gyrus, and fusiform gyrus, Jermakowicz et al found that there was a significant correlation between volume of ablation of the mesial hippocampus (but not total ablation volume) and seizure outcome . The best results were recently reported by Donos et al; 79.5% of 39 patients were free of disabling seizures at 6‐month follow‐up, with continued 67.4% at 20.3 ± 13.8 (SD) months . Could this be related to volumes of structures ablated?…”
Section: What Is To Be Learned About “Optimal Extent” From Laser Ablamentioning
confidence: 94%
“…This suggests a complex correlation that may be affected by other, as yet undefined, ablation parameters as well as patient selection. Furthermore, the total ablation volume of the hippocampal ablation does not correlate with seizure‐freedom rate, despite correction for preoperative anatomic volume . The extent of hippocampal resection in the open surgical literature has also failed to show a significant correlation with seizure‐freedom rates in MTLE .…”
Section: Discussionmentioning
confidence: 95%
“…Single‐center case series report that LITT for MTLE is a safe and effective first‐line alternative to open temporal lobe surgery in cases of mesial temporal sclerosis or where mesial temporal seizure onset has been proven by SEEG . A recent meta‐analysis of LITT for MTLE has suggested an overall seizure freedom rate of 50% at 12‐36 months, rising to 62% when considering “lesional” cases only .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation